The City of Constantinople Prelude the Ottoman Era Through the Travelogue "Nasab al-Akhbar wa Tadhkirat al-Akhyaar" by Hajj Abdullah Ibn al-Sabbah al-Andalusi - بلحاج نذير; زرمان محمّد (Milev Journal of Research and Studies, 2023)
The travel literature – in addition to being a source of pleasure and aesthetic - is considered as a very rich written source if one wants to know about the conditions of societies and civilizations and their material and moral achievements. The present work falls within this field, as we sought to present and describe what was mentioned about the city of Constantinople in the travelogue "Nasab al-Akhbar wa Tadhkirat al-Akhyaar" by Ibn al-Sabbah al-Andalusi, and then critique it based on some mechanisms of historical criticism. Our aim was to understand and determine the validity of the content mentioned by Ibn al-Sabbah related to the city of Constantinople, following an introduction to him and his travelogue. At the end of the research, some of the content was confirmed and considered a knowledge contribution provided by travel literature. However, other content was refuted and corrected in certain areas. Additionally, the research contributed to increasing our knowledge of Ibn al-Sabbah al-Andalusi and acknowledging him as one of the most prolific Arab travelers in terms of covering distances.